Hepatic rupture in a patient with severe pre-eclampsia and Hellp syndrome - Marroquín, Paul (2015)
Spontaneous hepatic rupture is a rare complication with high mortality associated to Hellp syndrome and severe pre-eclampsia. Hepatic rupture incidence is 1 in 45 000 to 1 in 225 000 pregnancies. We present institutional experience in managing hepatic rupture associated to severe pre-eclampsia and Hellp syndrome in a 29 year-old woman with 39 weeks gestation admitted to emergency by uterine contractions. After three hours she presented epigastralgia, right arm pain and low platelets that led to emergency cesarean section with Apgar 8 and 9 newborn. Hemoperitoneum, discontinuity of Glisson’s capsule and hepatic hematoma were found. Hepatic tamponage was performed and removed the fourth day with successful evolution.